(untitled) (American Journal of Islam and Society, 2023)
In this paper, I will explain why the lack of debate between political theory and comparative politics has led to an inadequate understanding of the politics of traditional Islamic scholars and Islamists in American political science. In the first section, I analyze the impact of the text-based approach of political theory; in the second, of the liberal frameworks of comparative politics; and in the third, a promising new development: the interdisciplinary field of Islamic legal studies, which has the potential to bridge the division between political science, law, and area studies approaches to the study of Muslim societies. I argue that the reliance of political theorists on seminal Islamist texts, rather than on the interpretations of texts during legal and political processes, limits their ability to represent the evolution of pragmatic Islamist theory in countries such as Pakistan. Moreover, whereas political theorists, such as Lucas Swaine, have demonstrated the futility of applying liberal assumptions to theocrats, comparativists continue to predominantly rely on liberal categories and frameworks, which produces a distorted view of Islamists. The division of labor between political theory and comparative politics, and the lack of conversation that results from it, makes it difficult—if not impossible—to fairly represent or analyze contemporary Islamist groups in American political science.